EXPERIMENTAL STUDIES OF THE BAISHESHEK BARLEY GRAIN PROCESSED BY THE ION-OZONE MIXTURE - Iztayev, A.; Baibatyrov, T.; Mukasheva, T.; Muldabekova, B.; Yakiyayeva, M. (Periodico Tche Quimica, 2020)
The article presents the results of an experimental study of Baisheshek barley grain treated with an ion-ozone mixture. This study aims to develop an innovative technology for processing barley with an ion-ozone mixture in order to increase their technological parameters, yield, quality, and grain safety. Kazakhstan has sharply increased the export of barley, and all agronomists, producers, and breeders are actively moving to the cultivation of this crop, while increasing production, productivity, improving product quality, reducing their losses and ensuring storage safety are an urgent task. Microorganisms play an important role during storage, they fall into crop production in a variety of ways, and if they fall into unfavorable storage conditions after harvesting, crop production quickly deteriorates, harmful substances such as toxins, mold, and others accumulate in it, which reduces the commodity value. To solve these problems, experimental studies were conducted on barley of the Baisheshek cultivar treated with an ion-ozone mixture with and without using excess pressure (cavitation). The calculated full-factorial design of experiments of the 2(3) (8 experiments) and 2(4) (16 experiments) degrees made it possible to obtain regression equations describing the change in the seed, physico-biochemical, and physiological properties of barley of the Baisheshek variety. В статье представлены результаты экспериментального исследования зерна ячменя Байшешек, обработанного ионно-озоновой смесью. Целью данного исследования является разработка инновационной технологии обработки ячменя ионно-озоновой смесью с целью повышения их технологических параметров, урожайности, качества и безопасности зерна. Казахстан резко увеличил экспорт ячменя, и все агрономы, производители и селекционеры активно переходят на выращивание этой культуры, при этом повышение производства, урожайности, улучшение качества продукции, снижение ее потерь и обеспечение безопасности хранения являются актуальной задачей. Микроорганизмы играют важную роль при хранении, они попадают в растениеводство различными способами, и если после сбора урожая попадают в неблагоприятные условия хранения, урожайность сельскохозяйственных культур быстро ухудшается, в нем накапливаются вредные вещества, такие как токсины, плесень и другие, которые снижает товарную стоимость. Для решения этих задач были проведены экспериментальные исследования на ячмене сорта Байшешек, обработанном ионно-озоновой смесью с применением и без использования избыточного давления (кавитации). Рассчитанный полнофакторный план экспериментов 2 (3) (8 опытов) и 2 (4) (16 опытов) степеней позволил получить уравнения регрессии, описывающие изменение посевных, физико-биохимических и физиологических свойств семян. ячмень сорта Байшешек.
Keywords: импакт-фактор 2020; томсон; периодическое издание; научный журнал; дальнее зарубежье; q2; процентиль 70; ячмень байшешек; зерновые культуры; качество зерна; урожайность зерна